Preparation method of high-heat-dissipation wear-resistant transparent conductive film
By using sol coating with components such as ethylenediaminetetraacetic acid in transparent conductive film materials and performing vacuum high-temperature annealing treatment, the limitations of existing transparent conductive film materials in terms of conductivity and service life are solved, and a high heat dissipation, wear-resistant and transparent conductive film is achieved, with good conductivity, stability and environmental protection.
Patent Information
- Application Number
- CN202510411095.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-07-01
AI Technical Summary
The existing transparent conductive film materials have limitations in their conductivity and service life, and the organic solvents used during the preparation process are harmful to the environment and health.
By placing sols with aqueous ethylenediaminetetraacetic acid solution, zinc acetate, magnesium acetate, alumina and glucose, coating and vacuum high-temperature annealing, a multi-layer structure C/MgZnO:Al transparent conductive composite film was prepared.
It realizes a high heat dissipation, wear-resistant and transparent conductive film, with good conductivity, stability and environmental protection, low cost, non-toxic and pollution-free.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive thin film materials, and particularly to a preparation method of a highly heat-dissipating, wear-resistant, and transparent conductive thin film. Background Art
[0002] Transparent conductive thin films have been widely used in recent years as electrode materials for solar cells, displays, gas sensors, etc. Currently, the most widely used transparent conductive thin film is the In2O3:Sn (ITO) thin film. However, its raw material In is an expensive and rare element, which limits its practical application potential. Recently, it has been found that ZnO thin films have the characteristics of high transmittance and low resistance comparable to those of ITO thin films, and the raw materials are abundant and the price is low, making them promising ideal materials to replace ITO. However, most of the ZnO films prepared by the sol-gel method currently use organic solvents, which are easy to cause harm to the body if not properly protected, and there are also many limitations in terms of electrical conductivity and service life. Based on this, it is particularly important to invent a highly heat-dissipating, wear-resistant, transparent conductive thin film that is durable, highly conductive, and non-toxic. Summary of the Invention
[0003] The purpose of the present invention is to provide a preparation method of a highly heat-dissipating, wear-resistant, and transparent conductive thin film to solve the problems existing in the prior art.
[0004] To solve the above technical problems, the present invention provides the following technical solution: A preparation method of a highly heat-dissipating, wear-resistant, and transparent conductive thin film, comprising the following steps: (1) After wiping the substrate clean, ultrasonically clean it in acetone solution, absolute ethanol, and deionized water in sequence for 10 - 20 min, and finally rinse it with deionized water and dry it in an oven for standby; (2) Place 30 - 90 parts of an ethylenediaminetetraacetic acid aqueous solution in a container, add 0.5 - 3 parts of zinc acetate, 0.2 - 1.2 parts of magnesium acetate, 0.03 - 0.24 parts of alumina, and 0.5 - 2 parts of glucose to prepare a solution. While stirring, dropwise add ammonia water solution until the pH value is 6 - 8, and continue to stir at 60 - 80 °C for 2 - 4 h to obtain a viscous colloidal liquid; (3) Immerse the pretreated substrate in the sol prepared in (2) to uniformly coat the film. After standing for 1 - 2 h, place it in a vacuum furnace and treat it at 300 - 400 °C for 0.5 - 1 h and then take it out; (4) Repeat step (3) to prepare a multi-layer composite film; (5) Place the obtained composite film in a tube furnace and anneal it at a high temperature of 300 - 500 °C to obtain a highly heat-dissipating, wear-resistant, and transparent conductive thin film.
[0005] Further, in the step (1), the substrate includes a polymer, glass, ceramic, or metal.
[0006] Further, the preparation method of the ethylenediaminetetraacetic acid aqueous solution in the step (2) is as follows: Add 0.5 - 1.5 parts of NaOH or KOH solution to 1 part of ethylenediaminetetraacetic acid, then add water until the pH value is 7 - 9, and stir until completely dissolved.
[0007] Further, the concentration of the NaOH or KOH solution is 5 - 15 M.
[0008] Further, glucose in the step (2) can be replaced by other organic carbon sources, such as one or several of citric acid, vitamin C, polydopamine, sugars, polyvinyl alcohol, tannic acid, resorcinol - formaldehyde resin, polyethylene glycol, asphalt, polypyrrole, polyvinylpyrrolidone, anthracene, and aniline.
[0009] Further, the dropping rate of ammonia water in the step (2) is 0.1 - 0.5 mL / min, and the rotation speed of the stirring is 600 - 1400 rpm.
[0010] Further, the film coating in the step (3) is to immerse for 1 - 3 min and then lift at a speed of 5 mm / min.
[0011] Further, the vacuum degree in the step (3) is 1×10 -4 ~7×10 -4 Pa.
[0012] Further, the final thickness of the film after repeating the process in the step (4) is 150 - 600 nm, and the optimal thickness is 400 nm.
[0013] Further, the specific operation of the high - temperature annealing treatment in the step (5) is as follows: Heat to 300 - 500 °C at a rate of 13 °C / min and hold for 12 h; The protective gas is an inert gas Compared with the prior art, the beneficial effects achieved by the present invention are: After the present invention is processed through steps such as configuring into a sol, film coating, drying, and vacuum annealing in sequence, a transparent conductive composite film of C / MgZnO:Al with a multi - layer structure is prepared to achieve the effects of high durability, good conductivity, low cost, non - toxicity, and no pollution.
[0014] First, using water as a solvent to reduce costs, adding zinc acetate to inhibit solid - phase diffusion and improve the film quality. Secondly, adding magnesium acetate to increase the band gap width of the film and have a higher visible light transmittance. Then, adding alumina to replace the lattice of Zn to increase the carrier concentration and reduce the resistance. Then, adding glucose as a carbon source, which is decomposed at high temperature and coated on the surface of metal ions to obtain better conductivity. After mixing evenly, a metal ion mixture solution is obtained. Using ethylenediaminetetraacetic acid as a complexing agent, with Zn 2+ ,Mg 2+ ,Al3+ Effectively combine, finally add ammonia water dropwise to buffer the pH value to 6 - 8 to promote the formation of subsequent gel, with better stability, and stir at a constant temperature for 2 - 4 h to obtain a viscous colloidal solution.
[0015] Secondly, evenly coat the sol on the substrate and let it stand for drying to avoid film cracking. Then, through vacuum high-temperature pretreatment, evaporate the residual solvent on the substrate to decompose the hydrolysis intermediate to generate ZnO crystal nuclei. At this time, the carbon source gradually decomposes to generate C in an anaerobic environment and uniformly coats the formed crystal grains to optimize the film strength. After repeating the treatment 3 - 5 times, a multi-layer structure is formed, constructing a three-dimensional conductive network of carbon, enhancing the carrier transport speed in the film, and improving the conductivity of the composite film material. Finally, high-temperature annealing further increases the ZnO crystal grains, reduces the pores of the porous film, causes densification shrinkage, and enhances the film strength. Specific embodiments
[0016] The following will describe clearly and completely the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts shall fall within the protection scope of the present invention.
[0017] In order to more clearly illustrate the method provided by the present invention, the following examples are used for detailed description. For the test of each index of the high heat dissipation and wear-resistant transparent conductive film prepared in the following examples, GBT26598 - 2011 is referred to.
[0018] Example 1 (1) Wipe the ceramic piece clean and then perform ultrasonic cleaning in acetone solution, absolute ethanol, and deionized water for 10 min in sequence. Finally, rinse with deionized water and dry in an oven for standby; (2) Add 0.5 parts of 5M NaOH solution to 1 part of ethylenediaminetetraacetic acid, then add water to a pH value of 7, and stir until completely dissolved to obtain an ethylenediaminetetraacetic acid aqueous solution; (3) Place 30 parts of the ethylenediaminetetraacetic acid aqueous solution in a container, add 0.5 parts of zinc acetate, 0.2 parts of magnesium acetate, 0.03 parts of alumina, and 0.5 parts of glucose to prepare a solution. While stirring at a speed of 600 rpm, add ammonia water dropwise at a speed of 0.1 mL / min to a pH value of 6, and continue stirring at 60 °C for 2 h to obtain a viscous colloidal liquid; (4) Immerse the pretreated ceramic piece in the sol prepared in (3) for 1 min, then lift it at a speed of 5 mm / min, let it stand for 1 h, and then place it in a vacuum furnace. At a vacuum degree of 1×10 -4 Pa, treat at 300 °C for 0.5 h and take it out; (5) Repeat step (4) to prepare a multilayer composite film with a thickness of 150 nm; (6) Place the obtained composite film in a tube furnace and heat it to 300 °C at a rate of 13 °C / min under argon protection and hold for 12 h to obtain a highly heat-dissipating, wear-resistant, and transparent conductive film.
[0019] Example 2 (1) Wipe the glass slides clean and then ultrasonically clean them in acetone solution, absolute ethanol, and deionized water for 10 min successively. Finally, rinse with deionized water and dry in an oven for standby; (2) Add 1 part of 10 M NaOH solution to 1 part of ethylenediaminetetraacetic acid, then add water to a pH value of 8 and stir until completely dissolved to obtain an ethylenediaminetetraacetic acid aqueous solution; (3) Place 60 parts of the ethylenediaminetetraacetic acid aqueous solution in a container, add 1.75 parts of zinc acetate, 0.7 part of magnesium acetate, 0.14 part of aluminum oxide, and 1.25 parts of glucose to prepare a solution. While stirring at a speed of 1000 rpm, dropwise add ammonia water at a rate of 0.3 mL / min until the pH value reaches 7, and continue to stir at 70 °C for 3 h to obtain a viscous colloidal liquid; (4) Immerse the pretreated glass slides in the sol prepared in (3) for 2 min, then pull them up at a speed of 5 mm / min. After standing for 1.5 h, place them in a vacuum furnace, and treat them at a vacuum degree of 4×10 -4 Pa and 350 °C for 0.75 h and then take them out; (5) Repeat step (4) to prepare a multilayer composite film with a thickness of 400 nm; (6) Place the obtained composite film in a tube furnace and heat it to 400 °C at a rate of 13 °C / min under nitrogen protection and hold for 12 h to obtain a highly heat-dissipating, wear-resistant, and transparent conductive film.
[0020] Example 3 (1) Wipe the polyethylene sheets clean and then ultrasonically clean them in acetone solution, absolute ethanol, and deionized water for 10 min successively. Finally, rinse with deionized water and dry in an oven for standby; (2) Add 1.5 parts of 15 M NaOH solution to 1 part of ethylenediaminetetraacetic acid, then add water to a pH value of 9 and stir until completely dissolved to obtain an ethylenediaminetetraacetic acid aqueous solution; (3) Place 90 parts of the ethylenediaminetetraacetic acid aqueous solution in a container, add 3 parts of zinc acetate, 0.7 part of magnesium acetate, 0.24 part of aluminum oxide, and 2 parts of glucose to prepare a solution. While stirring at a speed of 1500 rpm, dropwise add ammonia water at a rate of 0.5 mL / min until the pH value reaches 8, and continue to stir at 70 °C for 4 h to obtain a viscous colloidal liquid; (4) Immerse the pretreated polyethylene sheet into the sol prepared in (3). After immersion for 3 min, lift it at a speed of 5 mm / min, let it stand for 2 h, then place it in a vacuum furnace, and take it out after treating at a vacuum degree of 7×10 -4 Pa and 400 °C for 1 h; (5) Repeat step (4) to prepare a multilayer composite film with a thickness of 600 nm; (6) Place the obtained composite film in a tube furnace, heat it to 500 °C at a rate of 13 °C / min under nitrogen protection, and hold for 12 h to obtain a highly heat-dissipating, wear-resistant, and transparent conductive film.
[0021] Comparative Example 1 The difference between Comparative Example 1 and Example 2 lies only in step (3). Modify step (3) as follows: Place 60 parts of an ethylenediaminetetraacetic acid aqueous solution in a container, add 1.75 parts of zinc acetate, 0.7 parts of magnesium acetate, and 0.14 parts of aluminum oxide to configure a solution, and dropwise add an ammonia aqueous solution to a pH value of 7 at a stirring speed of 1000 rpm at a rate of 0.3 mL / min, and continue stirring at 70 °C for 3 h to obtain a viscous colloidal liquid. The remaining preparation steps are the same as those in Example 2.
[0022] Comparative Example 2 The difference between Comparative Example 2 and Example 2 lies only in step (3). Modify step (3) as follows: Place 60 parts of an ethylenediaminetetraacetic acid aqueous solution in a container, add 1.75 parts of zinc acetate, 0.7 parts of magnesium acetate, and 1.25 parts of glucose to configure a solution, and dropwise add an ammonia aqueous solution to a pH value of 7 at a stirring speed of 1000 rpm at a rate of 0.3 mL / min, and continue stirring at 70 °C for 3 h to obtain a viscous colloidal liquid. The remaining preparation steps are the same as those in Example 2.
[0023] Comparative Example 3 The difference between Comparative Example 3 and Example 2 lies only in step (3). Modify step (3) as follows: Place 60 parts of an ethylenediaminetetraacetic acid aqueous solution in a container, add 1.75 parts of zinc acetate, 0.14 parts of aluminum oxide, and 1.25 parts of glucose to configure a solution, and dropwise add an ammonia aqueous solution to a pH value of 7 at a stirring speed of 1000 rpm at a rate of 0.3 mL / min, and continue stirring at 70 °C for 3 h to obtain a viscous colloidal liquid. The remaining preparation steps are the same as those in Example 2.
[0024] Comparative Example 4 The difference between Comparative Example 4 and Example 2 lies only in step (3). Modify step (3) as follows: Place 60 parts of an aqueous solution of ethylenediaminetetraacetic acid in a container, add 0.7 part of magnesium acetate, 0.14 part of alumina, and 1.25 parts of glucose to prepare a solution. While stirring at a speed of 1000 rpm, add an aqueous ammonia solution dropwise at a rate of 0.3 mL / min until the pH value reaches 7, and continue stirring at 70 °C for 3 h to obtain a viscous colloidal liquid. The remaining preparation steps are the same as those in Example 2.
[0025] Comparative Example 5 The difference between Comparative Example 5 and Example 2 lies only in step (5). Modify step (5) as follows: Do not repeat step (4). The remaining preparation steps are the same as those in Example 2.
[0026] Comparative Example 6 The difference between Comparative Example 6 and Example 2 lies only in step (4). Modify step (4) as follows: Immerse the pretreated glass slide in the sol prepared in (3) for 2 min, then lift it at a speed of 5 mm / min, and let it stand for 1.5 h. The remaining preparation steps are the same as those in Example 2.
[0027] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that there is no step (6). The remaining preparation steps are the same as those in Example 2.
[0028] Effect Example The following Table 1 shows the performance analysis results of the high heat-dissipating and wear-resistant transparent conductive films of Examples 1 to 3 and Comparative Examples 1 to 7 of the present invention.
[0029] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the present invention uses glucose, which is uniformly coated on the surface of metal ions after high-temperature decomposition, increasing the mobility between electrons and showing better conductivity; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that alumina successfully replaces the lattice of Zn, increasing the carrier concentration and significantly reducing the resistance; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the addition of magnesium acetate increases the band gap width of the thin film and obtains better visible light transmittance; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the addition of zinc acetate reduces solid-phase diffusion and effectively improves the service life of the material. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that repeated coating can form a multi-layer structure, build a three-dimensional conductive network of carbon, and improve the conductivity of the thin film material. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 6, it can be found that high-temperature pretreatment can remove the residual solvent on the substrate, avoid film cracking during subsequent annealing, enhance the film firmness, and at the same time the carbon source is fully decomposed and uniformly coated outside the crystal grains, improving the conductivity. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 7, it can be found that high-temperature annealing densifies and shrinks the material, and significantly improves the strength.
[0030] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or basic characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present invention. Any reference signs in the claims should not be regarded as limiting the claimed claim.
Claims
1. A method for preparing a high heat dissipation wear-resistant transparent conductive film, characterized in that: The method comprises the following preparation steps: After wiping the glass slide clean, ultrasonically clean it in acetone solution, anhydrous ethanol and deionized water for 10 min in sequence, and finally rinse it with deionized water and dry it in an oven for later use; Add 1 part of 10M NaOH solution to 1 part of ethylenediaminetetraacetic acid, add water to a pH value of 8, and stir until completely dissolved to obtain an ethylenediaminetetraacetic acid aqueous solution; 60 parts of ethylenediaminetetraacetic acid aqueous solution were placed in a container, 1.75 parts of zinc acetate, 0.7 parts of magnesium acetate, 0.14 parts of aluminum oxide, and 1.25 parts of glucose were added to prepare a solution, and an ammonia aqueous solution was added dropwise at a rate of 0.3 mL / min under a stirring speed of 1000 rpm until the pH value reached 7, and the stirring was continued at 70°C for 3 hours to obtain a viscous colloidal liquid; The pretreated glass sheet was immersed in the sol prepared in (3) for 2 min and then pulled up at a speed of 5 mm / min. After standing for 1.5 h, it was placed in a vacuum furnace and heated at a vacuum degree of 4 × 10 -4 Pa, treated at 350℃ for 0.75h and then taken out; Repeat step (4) to prepare a 400 nm thick multilayer composite film; The obtained composite film was placed in a tubular furnace and heated to 400°C at a rate of 13°C / min under nitrogen protection and maintained for 12 h to obtain a high heat dissipation, wear-resistant and transparent conductive film.